Carcass and meat quality of lambs fed with sunflower seed or oil (Research, Society and Development, 2020)
The objective of this study was to compare the use of sunflower seeds and oil as a fat source in the diets of finishing lambs. Twelve crossbred Santa Inês × Dorper lambs, with an average initial weight of 22.10 ± 3.82 kg were housed in individual pens and divided into two treatments: diets with sunflower seeds or oil. The total diet of both groups contained 33% roughage (tifton grass hay 85) and 67% concentrate. The proportion of sunflower oil and seeds in the total dry matter of the diets was 1.83% and 5.51%, respectively for the treatments oil and seed. The experimental period lasted for 75 days. The animals were slaughtered when they reached an average live weight of 35 kg. The carcass and meat variables were not different between the treatments studied. The presence of oil or sunflower seeds in the diets, both with a high level of concentrate (67%), did not influence the pH values of the meat, with average values of 5.8 and 5.6, respectively. The use of 5.5% sunflower seed, or 1.8% sunflower oil, as fat sources in diets of crossbred Santa Inês X Dorper lambs in finishing, were effective to obtain quality meat and carcasses.